Association Between BMP2 Functional Polymorphisms and Sheep Tail Type - Zengkui Lu; Jianbin Liu; Jilong Han; Bohui Yang (Animals, 2020)
Bone morphogenetic protein 2 (BMP2) is strongly selected in both fat-tailed and thin-tailed sheep and may be a candidate gene for sheep tail type selection. However, the mechanism of action of BMP2 in sheep tail fat deposition remains unclear. This study investigated genetic variation and haplotype combinations of the BMP2 gene in sheep with different tail types, aiming to reveal the molecular mechanism of BMP2 in sheep tail fat deposition. We detected a total of three single nucleotide polymorphisms (SNPs) (g.48401619 T > A, g.48401272 C > A, and g.48401136 C > T) among 533 sheep. The alleles and genotype frequencies of these SNPs were in Hardy–Weinberg equilibrium and showed significant correlations with tail length. Linkage disequilibrium existed between the g.48401272 C > A and g.48401136 C > T sites, where CACT was the predominant genotype. At the cellular level, the expression levels of peroxisome proliferator-activated receptor gamma (PPARγ) and lipoprotein lipase (LPL) were upregulated after BMP2 overexpression; there were significantly higher levels of PPARγ than controls at 0 d and 1 d, and of LPL than controls at 1 d and 7 d. These results indicate that the BMP2 gene may participate in sheep tail fat deposition and could be used for molecular-marker-assisted selection of sheep tail type.